Digitalization Trends and Their Possible Implications to SME Performance: Comparative Study Between Hungary and Azerbaijan - Mahmudova, Leyla (International Journal of Engineering and Management Sciences, 2023)
This comparative research intends to find similarities and differences in the digitalization level of Hungary and Azerbaijan. Following the state of art in digitalization, further focus is on the digitalization of small and medium enterprises in both countries. The secondary research is done through several international reports and databases collected for years 2018-2022, depending on the availability. The comparison is performed based on four subcategories of digitization areas defined by the European Commission. The study holds its uniqueness due to the absence of comparative research between the mentioned two countries and the indicators used. The results contribute to the awareness, existing knowledge and provide future research insights into digitalization trends of both countries.